Effect of Physical activity on Insulin Resistance, Inflammation and Oxidative Stress in Diabetes Mellitus - Venkatasamy, Vighnesh Vetrivel (JCDR Research and Publications (P) Limited, 2013)
Diabetes Mellitus is a growing health concern projected to affect 366 million people worldwide by around 2030. Multiple approaches to address this health concern are documented; amongst which increased the habitual physical activity has been shown to be beneficial. Various mechanisms demonstrated show improvement of cellular insulin sensitivity. The interplay between insulin sensitivity and insulin resistance plays a key role in development and persistence of the diabetic state, which can be directly linked to the levels of physical activity. Regulation of adiponectin and leptin levels are also linked to physical activity via reduction of central obesity. Inflammatory markers, free radical reduction and up-regulation of physiological antioxidant processes are also observed in subjects with increased physical activity schedules, all of which play a significant role in the pathogenesis of Diabetes Mellitus.